Religiosity as a Moderator Between Planned Behavior Factors and Online Purchase Intention (IQTISHADIA, 2024)
The development of the digital era has changed consumer behavior patterns. This is influenced by factors such as social media, ease of use, lifestyle, and price. This study aims to evaluate the influence of social media, ease of use, price, lifestyle, and religiosity on online shopping behavior. This study uses Structural Equation Modeling (SEM) with a quantitative approach to measure the influence of social media, ease of use, price, lifestyle and religiosity on 300 Muslim consumer respondents with religiosity as a moderator variable. This study found that social media, ease of use, price, and lifestyle have a significant impact on online shopping behavior, with a p-value below 0.05. Price shows the strongest influence (coefficient 0.328), followed by ease of use (0.261), social media (0.219), and lifestyle (0.132). In contrast, religiosity has no significant influence (p-value 0.954) and does not moderate this relationship, as indicated by the high p-value and low f-square value. This suggests that Muslim consumers prioritize rational factors over religiosity in online shopping.